Rechter Commisaris: A Dull Sword or A Medicine to Justice? - Reynaldo Arya (President University, 2018)
In order to protect the fundamental rights of a human being from any violations during the process of investigation or trial proceedings, an institution called praperadilan was established through Indonesia Criminal Procedural Law. However, throughout 38 years of this institution implementation in Indonesia, the flaw and weakness of this institution has been identified. The example of weakness themselves posed as a great danger to the human rights of the suspect of accused, as on conducting coercive measures, the law enforcement may conduct the measures not in accordance with the law. This weakness has soon lead the society to thought of an alternative towards this institution, another institution that is better and may solve the weakness posed by praperadilan. The society then turn back to the history, realizing that prior to the implementation of Herziene Indische Reglement (HIR) in 1941 has erase a similar institution with the same purpose as in praperadilan, this institution was commonly known as “Rechter Commisaris”. In order to understand whether this reestablished institution may solve the weakness of praperadilan, the author decides to conducting a research on this topic through implementing normative legal method to procure the necessary materials. This writing will analyze the present status quo of praperadilan through understanding the changes made by Constitutional Court to this institution and identifying the weakness of praperadilan that still relevant in 2019. Then, this writing will further analyze the reasons behind the disappearance of this institution in HIR and Law Number 8 Year 1981 regarding Criminal Procedural Law. Finally, this writing will provide a comprehensive comparison and analysis on whether the present reestablished Rechter Commisaris that was contained within 2011 Draft of Criminal Procedural Law may lead to better protection of fundamental rights of a human being.